1991
DOI: 10.1104/pp.97.1.94
|View full text |Cite
|
Sign up to set email alerts
|

A Lipoxygenase Pathway Is Activated in Rice after Infection with the Rice Blast Fungus Magnaporthe grisea

Abstract: Lipoxygenase (LOX) and lipid hydroperoxide-decomposing activity (LHDA) markedly increased in the fifth leaves of rice (Oryza sativa cv Aichiasahi) after infection with the rice blast fungus, Magnaporthe grisea. The increases in the enzyme activities were significantly higher in response to infection with an incompatible strain (race 131) compared with infection with a compatible strain (race 007) of the fungus. Using ion-exchange chromatography, we isolated three LOX activities (leaf LOX-1, -2, -3) from both u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 21 publications
2
59
0
1
Order By: Relevance
“…Despite these similarities and the reported homologies between tobacco genomic DNA sequences and soybean seed lipoxygenase cDNA (Bookjans et a/., 1988), the elicitor-induced tobacco lipoxygenase did not cross-react with antibodies against soybean seed lipoxygenase. Some physicochemical parameters of the rice lipoxygenase activity, reported to increase during infection, have been described (Ohta et a/., 1991); they exhibited no similarity with the induced tobacco enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these similarities and the reported homologies between tobacco genomic DNA sequences and soybean seed lipoxygenase cDNA (Bookjans et a/., 1988), the elicitor-induced tobacco lipoxygenase did not cross-react with antibodies against soybean seed lipoxygenase. Some physicochemical parameters of the rice lipoxygenase activity, reported to increase during infection, have been described (Ohta et a/., 1991); they exhibited no similarity with the induced tobacco enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…In rice plant, it has been shown that 9(S),l2(S),l3(S)-trihydroxy-10(E)-octadecenoic acid has antifungal activity and is produced from plants suffering from rice blast disease (Kato et al, 1985(Kato et al, , 1991. Infection of rice with the rice blast fungus (Mugnaporthe grisea) results in activation of a lipoxygenase pathway (Ohta et al, 1991). Furthermore, oat leaves inoculated with an incompatible race of crown rust fungus (Puccinia coronata uvenae) respond with synthesis of lipoxygenase isoenzymes (Yamamoto and Tani, 1986).…”
Section: Epoxy-9(s)-hydroxy-lo(e)-octadecenoatementioning
confidence: 99%
“…This new pathway involves (a) a peroxygenase, which catalyzes an intramolecular transfer of one oxygen atom from fatty acid hydroperoxides, yielding an epoxyalcohol and Jor co-oxidation reactions such as epoxidation of double bonds of unsaturated fatty acids , and (b) an epoxide hydrolase, which preferentially hydrates the epoxides formed by the peroxygenase (Blée and Schuber, 1992a). Lipid-breakdown metabolism is generally enhanced under stress conditions (Ohta et al, 1991;Farmer and Ryan, 1992a;Croft et al, 1993;Choi et al, 1994). At present, it seems that peroxygenase and hydroperoxide lyase pathways are involved in the response to pathogen infection (Ohta et al, 1991;Croft et al, 1993), and the hydroperoxide dehydratase cascade operates in wound-response programs (Farmer and Ryan, 1992a;Choi et al, 1994).…”
mentioning
confidence: 99%
“…Lipid-breakdown metabolism is generally enhanced under stress conditions (Ohta et al, 1991;Farmer and Ryan, 1992a;Croft et al, 1993;Choi et al, 1994). At present, it seems that peroxygenase and hydroperoxide lyase pathways are involved in the response to pathogen infection (Ohta et al, 1991;Croft et al, 1993), and the hydroperoxide dehydratase cascade operates in wound-response programs (Farmer and Ryan, 1992a;Choi et al, 1994). Plant organelles such as chloroplasts may be a site of biosynthesis of regulatory molecules potentially involved in plant-defense reactions, since lipoxygenase, hydroperoxide lyase, and dehydratase activities have been measured in chloroplast preparations (Vick and Zimmerman, 1987;Bowsher et al, 1992;Hatanaka, 1993;Song et al, 1993).…”
mentioning
confidence: 99%